Rancang Bangun Aplikasi Pengelolaan Kendaraan Dinas Di Sub Bagian Sarana dan Prasarana (SUBBAGSARPRAS) Polres Sidoarjo - Cahyono, Ariuh Hadi Nur; Lusiani, Titik; Mujayana, Marya (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Currently, Sub section of Facilities and Infrastructure (SUBBAGSARPRAS) Sidoarjo Resort Police manages the data of the official vehicles totaled 570 units consisting of 466 units of two-wheel, 90 units of four-wheel, and 14 units of trucks. 2 officers of SUBBAGSARPRAS who manage the data have a problem that is the difficulty of finding data of official vehicle and vehicle duty holder, holders of the vehicles that must return the vehicles as much as 5% of the total official vehicle, official vehicles use permit that have been expired as much as 65%, the tax of official vehicles that have been expired as much as 45%, and the distribution of fuel oil. The difficulties are caused by the processing of the data is still not well organized. So the officers still often make mistakes in reporting the vehicle management agency results recap. Solutions to overcome these problems is an application that can manage data well. Thus a design and implementation of application is made to manage official vehicles in SUBBAGSARPRAS based on desktop by using the method of System Development Life Cycle (SDLC). Tthis research resulted in the design and implementation of application to manage official vehicles in SUBBAGSARPRAS Sidoarjo Resort Police. This application can manage official vehicles in SUBBAGSARPRAS Sidoarjo Resort Police and can generate a report on the vehicle management. Keywords: SUBBAGSARPRAS, System Development Life Cycle (SDLC), the official vehicles